Evaluation of dry specimen transport and processing time using an isothermal amplification high-risk human papillomavirus assay - Longhua Hu; Suhui Wu; Haixia Shang; Jerome Belinson; Jinhong Li; Xiaoqin Wu; Yaling Huang; Jingfen Sun (BMJ Publishing Group, 2022)
Background: Dry specimen transport has shown equivalence to traditional liquid transport using a novel high-risk Human papillomavirus assay. Considering that dry transport might cross obstacles during cervical cancer screening in low and middle resource settings, this study was designed evaluate different processing time of dry specimen transport using the same isothermal amplification hrHPV assay. Methods: There were 564 women between the ages of 30-55 recruited from colposcopy clinic. For each patient, two endocervical samples were collected and placed into empty collection tubes by physician. Samples were stored at room temperature until analyzed for hrHPV using the AmpFire assay at two time points: 2 days and 2 weeks. 511 of the 564 participants with positive hrHPV were provided colposcopy exam and quadrant biopsy. Results: A total of 1128 endocervical samples from 564 patients were detected by the Ampfire assay. Good agreement was found between two time periods (Kappa ​± ​Standard error ​= ​0.67 ​± ​0.04). Sensitivity (2days/2weeks) for CIN2+ was 95.28% (95% CI: 92.14%-98.42%) vs 90.57% (CI (86.65%-94.49%) and specificity (2days/2weeks) was 22.47% (CI 19.33%-25.61%) vs 28.15% (CI 24.23%-32.07%) respectively. The difference for Ampfire HPV detection in sensitivity for CIN2+ for the two time periods was not significant (P ​= ​0.227), while the difference in specificity for CIN2+ was significant (P ​= ​0.001). The difference in Ct values 29.23 (CI 28.15-30.31) and 29.27 (CI 28.19-30.35) between two time points was not significant (P ​= ​0.164). Conclusion: Processing dry brush specimens can be delayed up to 2 weeks. Using the AmpFire assay platform which supports cervical cancer prevention programs in low-to-middle-income countries (LMICs).